2010
DOI: 10.1007/s12598-010-0132-1
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and thermal expansion of 4J36/ZrW2O8 composites

Abstract: Gas atomized 4J36 alloy powder was milled for 72 h then mixed with ZrW 2 O 8 powder and sintered at 600C for 4 h under argon atmosphere. 4J36/ZrW 2 O 8 composites containing 10 vol.%, 20 vol.%, 30 vol.%, and 40 vol.% ZrW 2 O 8 were fabricated, the relative density of which ranged from 70% to 80%. Thermal expansion coefficients of the composites decreased as the amount of ZrW 2 O 8 increased, in agreement with the rule of the mixture. The coefficient of thermal expansion of the 4J36/40 vol.%ZrW 2 O 8 composite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 8 publications
0
4
0
1
Order By: Relevance
“…It should be possible to overcome this problem by using HfW 2 O 8 as a filler instead of ZrW 2 O 8 , however, no such attempts have been reported to date. An exploratory investigation on a ZrW 2 O 8 /low expansion steel composite (α steel = 1.5 × 10 −6 K −1 ) still observed formation of γ-ZrW 2 O 8 , clearly indicating that the application of ZrW 2 O 8 will be limited to environments that will not exert significant pressure on the filler particles [191]. …”
Section: Compositesmentioning
confidence: 99%
“…It should be possible to overcome this problem by using HfW 2 O 8 as a filler instead of ZrW 2 O 8 , however, no such attempts have been reported to date. An exploratory investigation on a ZrW 2 O 8 /low expansion steel composite (α steel = 1.5 × 10 −6 K −1 ) still observed formation of γ-ZrW 2 O 8 , clearly indicating that the application of ZrW 2 O 8 will be limited to environments that will not exert significant pressure on the filler particles [191]. …”
Section: Compositesmentioning
confidence: 99%
“…多种纤维混杂复合材料可以更好地实现热膨胀系数 调控. Praveen等人 [29] [30,31] , 因瓦合金 [32] 或铝 [33,34] , 氧化锆陶 瓷 [35,36] , 高分子聚合物 [37,38] 等作为正膨胀基体, 通过 合理配比及相应的制备工艺可以得到零或负膨胀复 合 材料 [39] . 其 他一 些颗粒 增强 复合材 料研 究包括 : Ding 等 人 [40] , Yan 等 人 [41] 分 别 制 备 了 近 零 膨 胀 的 Mn 3 Cu 0.5 A 0.5 N (A=Ni, Sn)/Cu和Mn 3 Cu 0.5 Ge 0.5 N/Cu复 合材料; Liu等人 [42] [43] [44] .…”
Section: 石英具有极小热膨胀系数 但这些材料的负、低热膨 胀效应只能保持在要么很低 要么很高的狭窄温度unclassified
“…To regulate the expansion coefficient in composite coatings, some scholars have introduced the negative thermal expansion material ZrW 2 O 8 . This helps control expansion behavior, reduce residual stresses, and achieve zero cracking of the laser fusion cladding layer [15][16][17][18]. Islam et al [19] showed that the inclusion of 1% ZrW 2 O 8 nanoparticles can decrease the degree of thermal expansion mismatch in carbon fiber-reinforced polymer composites during polymerization, thereby reducing thermal expansion mismatch in these composites.…”
Section: Introductionmentioning
confidence: 99%